Experience of treatment of presacral tumors - A. M. Kuzminov; S. A. Frolov; A. S. Borodkin; Yu. Yu. Chubarov; V. Yu. Korolik; Yu. F. Borisov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Improvement of presacral tumors treatment results.Material and methods. Data of surgical treatment 21 patients with true presacral tumors, operated in Federal government-financed institution «Ryzhikh State Scientific Center of Coloproctology», Ministry of healthcare of the Russian Federation with 2004 on 2013 was analyzed. Study group included 16 women (76%) and 5 men (24%) with mean age of 46,3±15,1 years.Results. Tumor relapse was revealed in 4 (5,6%) of operated patients, tumors in these cases had various histological structure.Conclusion. Experience of surgical interventions at benign retrorectal presacral tumors allows to consider surgical method as adequate treatment approach. The highest relapse rate was observed at malignant tumors; such patients require the combined treatment at specialized oncologic clinic. The choice of surgical access is determined, first of all, by neoplasm localization.